Displacement rate and structural effects on Poisson ratio of a ductile structural adhesive in tension and compression. (October 2017) - Angelidi, Myrsini; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract: The effects of the loading type, i.e. tension or compression, and displacement rate on the Poisson ratio of a non-linear viscoelastic ductile structural adhesive have been investigated using digital image correlation-based strain fields. The results showed that the Poisson ratio should be based on true strains to take geometry changes into account. In tension, the ratio exhibited a slight dependency on the true strain level below the yield point and on the displacement rate. The rate dependency was confirmed in regions with necking, where the Poisson ratio locally decreased. Subjected to compression, the ratio was affected by out-of-plane deformations of the specimens and thus exhibited values above 0.5. The necking in tension and out-of-plane deformations in compression may be considered as structural effects on the Poisson ratio that may be attributed to changes in the molecular structure of the polymer.